The Mediating Role of Attentional Control on the Relationship Between Multilingualism and Writing Ability of Iranian EFL Learners - Hamed Keramat; Sima Modirkhamene (International Journal of Practical and Pedagogical Issues in English Education)
Nowadays, most teachers and researchers are convinced that multilingual learners often achieve better additional language learning results than bi- and monolinguals; this superiority is often attributed to their cognitive and metalinguistic skills. One of the most important cognitive factors which is reported to be advantageous among multilingual learners is the notion of attentional control (AC), as one of the core executive functions (EFs). The present study was thus motivated to investigate the moderating role of AC on the writing proficiency including three CAF measures (complexity, fluency, and accuracy) of Iranian upper-intermediate trilingual learners in comparison to bilinguals. To this end, a total of 70 EFL learners from different language institutes in Shahindezh, including both males (N=31) and females (N=39) were conveniently selected to participate in this study. All the intended participants, aged 18-22, were categorized into two groups of Turkish-Persian and Kurdish-Persian bilinguals (N=36) and Turkish-Kurdish-Persian trilingual EFL learners (N=34) based on their responses to a tailor-made linguistic background information questionnaire. An adapted version of the First Certificate in English (FCE) test was also administered to assure homogeneity across the sample. Further data were collected through attentional control scale (ACS), developed by Derryberry & Reed (2002), and a topic writing task which was selected from TOEFL writing inventories. Results of an independent samples t-test indicated that trilingual learners, compared to their bilingual counterparts, have a higher level of attentional control ability. Furthermore, the results of three separate sets of ANCOVA revealed that: First, trilingual learners outperformed bilinguals in all CAF measures of writing proficiency and,  second, trilingual learners’ higher attentional control ability does not moderate their superior performance in CAF measures. In other words, the superior performance of trilingual learners in complexity, accuracy and fluency measures of writing proficiency, in this context, is not attributable to their attentional control ability. The results are discussed in relation to the significant role that EFL learners’ cognitive characteristics, possibly other than AC, and linguistic background may play in language learning in general, and writing proficiency in particular. Further implications for language teaching in multilingual contexts as well as recommendations for further research are also discussed in this study.